2003
DOI: 10.1136/bjo.87.6.784
|View full text |Cite
|
Sign up to set email alerts
|

View 2: The case for primary vitrectomy

Abstract: n emmetropic otherwise well 67 year old man, with no history of eye disease, presents with a rhegmatogenous retinal detachment. The patient needs surgery to repair the detachment. There are three major techniques available to repair the detachmentscleral buckling without drainage, primary vitrectomy, and pneumatic retinopexy. In determining which surgical technique to choose, there are a number of clinical features to consider

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, PPV is growing in popularity as a first-line procedure for primary RD, especially in pseudophakic patients (Lois and Wong 2003, SPR Study Group 2003). PPV has several advantages over SB (Table 1).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, PPV is growing in popularity as a first-line procedure for primary RD, especially in pseudophakic patients (Lois and Wong 2003, SPR Study Group 2003). PPV has several advantages over SB (Table 1).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“… Abbreviations: PPV/SB, combined pars plana vitrectomy/scleral buckling; PVR, proliferative vitreoretinopathy.Adapted from SPR Study Group (2003) and Schwartz and Flynn (2006).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Mehta et al [4] showed that the addition of the SB to PPV may decrease a risk for redetachment after repair of phakic RRD when compared to PPV alone. In pseudophakic patients, combined PPV and scleral buckling showed a trend toward achieving greater anatomic success rates [5, 6]. Alexander et al [7] found that supplementary scleral buckling improved and enhanced primary success rates in inferior break detachments over vitrectomy and gas without buckling.…”
Section: Introductionmentioning
confidence: 99%